2003
DOI: 10.4064/cm96-2-1
|View full text |Cite
|
Sign up to set email alerts
|

On some generalized Einstein metric conditions on hypersurfaces in semi-Riemannian space forms

Abstract: Abstract. Solutions of the P. J. Ryan problem as well as investigations of curvature properties of Cartan hypersurfaces and Ricci-pseudosymmetric hypersurfaces lead to curvature identities holding on every hypersurface M isometrically immersed in a semiRiemannian space form. These identities, under some assumptions, give rises to new generalized Einstein metric conditions on M . We investigate hypersurfaces satisfying such curvature conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 8 publications
0
49
0
Order By: Relevance
“…Examples of hypersurfaces satisfying (1.4) with ρ = 0 are presented [10] (see also [14]). It is known that such hypersurfaces are Ricci-pseudosymmetric (see e.g., [5]).…”
Section: 3) R · S = L S Q(g S)mentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of hypersurfaces satisfying (1.4) with ρ = 0 are presented [10] (see also [14]). It is known that such hypersurfaces are Ricci-pseudosymmetric (see e.g., [5]).…”
Section: 3) R · S = L S Q(g S)mentioning
confidence: 99%
“…We refer to [3] for a survey of results related to manifolds, and in particular to hypersurfaces satisfying pseudosymmetry type conditions. Hypersurfaces M in N n+1 s (c), n 4, having the tensor R · C expressed by a linear combination of the tensors Q(S, R), Q(g, R) and Q(S, G), were investigated in [16] (see also [10]). Among other things in [16] it was shown that such hypersurfaces M satisfy (1.5) on U H ⊂ M and in a consequence, they are Ricci-pseudosymmetric.…”
Section: 3) R · S = L S Q(g S)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypersurfaces M in N n+1 s (c), n ≥ 4, satisfying (9) on U H ⊂ M were investigated in many papers: [1], [3], [5]- [7], [9]- [13], [15], [17], [19]- [23] and [26]. These papers are also related to the P. J. Ryan problem (see e.g.…”
mentioning
confidence: 99%
“…In the paper [4] (Theorem 3.1) it was shown that on every hypersurface M in Np +1 (c) , n > 4, the following identity is satisfied…”
Section: Introductionmentioning
confidence: 99%